Quality Targets for Concentrations of Hazardous Substances in Surface Waters in Germany - Irmer, U.; Markard, C.; Blondzik, K.; Gottschalk, C.; Kussatz, C.; Rechenberg, B.; Schudoma, D. (Ecotoxicology and environmental safety, 1995)
During the past several years, in Germany, a federal government/federal states working group prepared a "guide document for the derivation of quality targets designed to protect inland surface waters against hazardous substances." In May 1993 the 40th Conference of Environment Ministers (Umweltministerkon-ferenz) adopted the guide document subject to further trial. Based on the guide document it will be possible to define water quality requirements in the field of water resources management, e.g., protection of aquatic communities and safeguarding of drinking water supply, as a complementing approach to existing statutory emission control regulations. The quality targets derived on the basis of the guide document define concentrations of hazardous substances in water, suspended particulate matter or sediments which should not be exceeded (guide values). According to current scientific knowledge, compliance with the quality targets ensures that a hazard to the protection-meriting uses considered need not be feared. Where quality targets are found to be exceeded, the causes should be explored. On that basis water pollution control and sanitation priorities can be defined more appropriately. In addition, the outlined approach to deriving quality targets provides a basis for characterizing water quality and is helpful in priority-setting with respect to analytical methods to be optimized.